Image processing for multi-mobile robot coordination - Luo, Beier (Nanyang Technological University, 2020)
This project aims to design image processing module for a multi-robot system consisting of multiple mobile robots. The multi-robot system consists of two prototypes built from DIY robot chassis, Raspberry Pi, Arduino Uno, motor driver and camera. Image processing methods are implemented for obstacle detection, avoidance and object tracking. The intention is for the multi-mobile robots to avoid obstacles in their path while moving together in a formation. The main chapters of this project include literature reviews on existing research, software and hardware designs, and evaluation of results from testing the robots. Finally,ends off with conclusion and recommendation for future improvements. Overall, this project has allowed the student to gain insights into multiple research fields such as computer vision, multi-mobile robot coordination and robot formation control.The student has developed a deeper understanding of how an engineer can combine and integrate knowledge from different fields to solve a problem.